2014
DOI: 10.1139/cgj-2012-0425
|View full text |Cite
|
Sign up to set email alerts
|

Deformations and ground temperatures at a road embankment in northern Canada

Abstract: The paper examines the behaviour of a highway embankment in an area of discontinuous permafrost about 18 km northwest of Thompson, Manitoba. Frequent maintenance has been required. Research involved site investigation, laboratory testing, installing instruments, data collection, and numerical modeling. The paper reports data from almost 3 years of observation. Measurements of ground temperatures suggest that formerly ice-rich foundation soil has thawed under the toe and side-slope. Approximate values of segreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Therefore, the freezing model of saturated coarse-grained soil in a closed system cannot be influenced by the properties of the soil. Furthermore, it can be seen that Equation 14is highly similar to the Clapeyron equation as shown in Equation (15). The Clapeyron equation can be applied to any pure substances at the state of the phase transition equilibrium.…”
Section: Freezing Model Of Saturated Coarse-grained Soilmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, the freezing model of saturated coarse-grained soil in a closed system cannot be influenced by the properties of the soil. Furthermore, it can be seen that Equation 14is highly similar to the Clapeyron equation as shown in Equation (15). The Clapeyron equation can be applied to any pure substances at the state of the phase transition equilibrium.…”
Section: Freezing Model Of Saturated Coarse-grained Soilmentioning
confidence: 89%
“…All of these viewpoints are reasonable, and the main reason for the difference is that the research purposes of these studies are different, and, in addition, the location of the research is different. However, there are insufficient systematic studies on the micro-formation mechanism of waterfall ice [15].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of temperature change on peak shear strength parameters has been investigated by a number of researchers (Batenipour et al, 2014;de Groot et al, 2015;Yavari et al, 2016;Ng et al, 2017). The in uence of this factor on various other parameters, such as consolidation properties, for example, was also a subject of some studies (Tsutsumi and Tanaka, 2012;Dalla Santa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the reliability implications associated with possible temperature impact on soil shear strength have been of most concern, for various reasons and under different conditions. Batenipour et al (2014) performed triaxial tests at the temperatures of 3°C and 21°C to verify whether tests at normal laboratory conditions (21°C) can be applicable to those in cold climate regions with average temperature of 3°C. It was concluded that the friction angle did not vary with the temperature, con rming the earlier ndings of Graham et al (2001).…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater flow paths and fluxes can be highly controlled by permafrost thaw (Walvoord et al ). Current and projected permafrost degradation under highway embankments, and other infrastructure projects, is also a continuing problem (Batenipour et al ; Flynn et al ; Mu et al ; Kurz et al ). A warming of approximately 0.3 °C per decade of the shallow permafrost in the northern and central Mackenzie region of the Northwest Territories (NWT) has taken place since the 1980s, which is tied to an increase in the mean annual air temperature (Beilman and Robinson ; Smith et al ).…”
Section: Introductionmentioning
confidence: 99%